Long Noncoding RNAs Responding to Ethanol Stress in Yeast Seem Associated with Protein Synthesis and Membrane Integrity - Schnepper, Amanda Piveta [UNESP]; Kubo, Agatha M. S. [UNESP]; Pinto, Camila Moreira [UNESP]; Gomes, Ramon Hernany Martins [UNESP]; Fioretto, Matheus Naia [UNESP]; Justulin, Luís Antonio [UNESP]; Braz, Aline M. M. [UNESP]; Golim, Marjorie de Assis [UNESP]; Grotto, Rejane M. T. [UNESP]; Valente, Guilherme Targino [UNESP] (MDPI, 2025)
Background/Objectives: Translation and the formation of membraneless organelles are linked mechanisms to promote cell stress surveillance. LncRNAs responsive to ethanol stress transcr_9136 of the SEY6210 strain and transcr_10027 of the BY4742 strain appear to act on tolerance to ethanol in these strains. Here, we investigate whether the ethanol responsiveness of transcr_9136 and transcr_10027 and their role in ethanol stress are associated with protein biogenesis and membraneless organelle assembly. Methods: SEY6210 transcr_9136∆ and BY4742 transcr_10027∆ and their wild-type counterparts were subjected to their maximum ethanol-tolerant stress. The expression of the transcr_9136, transcr_10027, ILT1, RRP1, 27S, 25S, TIR3, and FAA3 genes was accessed by qPCR. The level of DCP1a, PABP, and eIF4E proteins was evaluated by Western blotting. Bioinformatics analyses allowed us to check whether transcr_9136 may regulate the expression of RRP1 and predict the interaction between transcr_10027 and Tel1p. The cell death rate of SEY6210 strains under control and ethanol stress conditions was assessed by flow cytometry. Finally, we evaluated the total protein yield of all strains analyzed. Results: The results demonstrated that transcr_9136 of SEY6210 seems to control the expression of RRP1 and 27S rRNA and reduce the general translation. Furthermore, transcr_9136 seems to act on cell membrane integrity. Transcr_10027 of BY4742 appears to inhibit processing body formation and induce a general translation level. Conclusions: This is the first report on the effect of lncRNAs on yeast protein synthesis and new mechanisms of stress-responsive lncRNAs in yeast, with potential industrial applications such as ethanol production.
Keywords: CRISPR-Cas9; gene regulation; P-bodies; protein synthesis; ribosomal biogenesis; Saccharomyces cerevisiae; stress granules